Reframing the veil and liminal hybrid identities in selected contemporary immigrant Muslim women’s novels - Al-Karawi, Susan Taha Ahmed (2014)
This thesis explores the rapidly growing body of fiction in English by and about practising Muslim women living in Western societies. This exploration is made through the lives and works of three contemporary immigrant Muslim women writers: Randa Abdel-Fattah’s Does My Head Look Big in This? (2005), Leila Aboulela’s Minaret (2005), and Mohja Kahf’s The Girl in the Tangerine Scarf (2006). I argue that the in-between space characteristic of liminality and hybridity is a meaningful interpretive lens to understand the struggles resulting from the sacred space of being betwixt and between of wearing the veil by female protagonists. The three research objectives to make this argument are: To examine how the fictional characters challenge the stereotyped images of Muslim women in the West as depicted in the selected novels, to explore how the veil in the selected novels of Abdel-Fattah, Aboulela, and Kahf is used to signify the struggle of being betwixt and between and having a hybrid identity, and to discover how the authors’ personal experiences of immigration are significant in relation to their selected novels.The theoretical approaches used to understand the in-between space and struggle over identity is Victor Turner’s concept of liminality as it is theorised in his book The Ritual Process (1969) and Homi Bhabha’s hybridity and third space as conceptualised in his book The Location of Culture (1994). Methodologically, my study uses a close reading of the text, where passages are extracted from the novels and serve as evidence in my analysis. This approach allows for a textual analysis that explores changes in character identity over time. Liminality is conceptually framed to describe a ritual space and phase of transition in which a person experiences struggles, ambivalence, and alienation as a result of no longer being what they were, and do not have the comfort of being what they are yet to be. Hybridity is framed to mean a unique combination of identities that the protagonists develop as a result of their experiences with rejection, ambivalence, prejudice, and struggle related to how they frame wearing the Muslim veil. My study finds that the use of liminality, hybridity and third space as an analytical frame enables understanding of the inbetween space which female protagonists experience as they negotiate an identity that is both modern yet traditional, rather than an identity that is one or the other. I discovered that examining at what characters say and describe is necessary in order to discover the diversity and detail of their lives as Arab Muslim women living in the West and provides evidence to counter the overriding hegemonic narrative that they are all the same: oppressed. Future research should focus on a comparative examination of fiction that portrays the diversity of Muslim women in the Middle East in order to know if the experience of those women in the West are unique to the immigrant experience or something more general to Muslim women wherever they may live.